Projected Productive Age Population in East Kalimantan in 2040 - Adea; Trees Sandy, Aisyah; Ningrum, Mei Vita Romadon; Juwari (Sustainability (STPP) Theory, Practice and Policy, 2025)
The productive age refers to the population aged 15–64 years. This study aims to analyze the projection of the productive age population in East Kalimantan by the year 2040. This research employs a qualitative descriptive approach using a literature review method. The population and sample in this study are residents of East Kalimantan aged 15–64 years (productive age), with data collected through purposive sampling techniques and secondary sources. Data analysis was carried out using qualitative techniques based on the Miles and Huberman. The results indicate that East Kalimantan is projected to have a total population of 6,116,320 in 2040, with 4,223,680 individuals in the productive age group. This group is expected to experience the highest population growth rate and benefit from a significant demographic bonus. A large productive age population presents great potential for enhancing economic productivity; however, it may also pose social challenges if not accompanied by sufficient employment opportunities. Therefore, it is essential for the East Kalimantan government to develop inclusive policies that support education, skill development, and job creation to optimize the demographic bonus and minimize associated risks.